Seasonal Retail Franchise Identity and Its Spatial Functional Design: A Case Study on Ang-Kee's Snack Kiosk - Niphawan Sunthonovard; Nopadon Sahachaisaeree (My University, 2012)
Retail business has the environment reflect their unique identity. This research thus aims, firstly, to study the unique corporate retail identity. Secondly, it aims to examine the, type of product, sale activities, and storage system toward spatial needs of the sale environment. Finally, the research investigates the physical appearance conveying seasonal identity and meaning responsive to purchasers' perception towards the final design guideline recommendation. The research anticipates that the case study could find a pattern of how people perceive and react to the built environment, and it could also reveal a proper research methodology to reveal environment and behavior pattern.
Keywords: Interactive kiosk; Corporate identity; Franchise; Consumer Retail Behavior Studies